2022
DOI: 10.1109/taes.2022.3156087
|View full text |Cite
|
Sign up to set email alerts
|

When to Crossover From Earth to Space for Lower Latency Data Communications?

Abstract: For data communications over long distances, optical wireless satellite networks (OWSNs) can offer lower latency than optical fiber terrestrial networks (OFTNs). However, when is it beneficial to switch or crossover from an OFTN to an OWSN for lower latency data communications? In this work, we introduce a crossover function that enables to find the crossover distance, i.e., a distance between two points on the surface of the Earth beyond which switching or crossing over from an OFTN to an OWSN for data commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In [14], crossover functions were proposed to enable the calculation of the crossover distance in four different scenarios. It was concluded that the crossover distance depended upon the altitude of satellites in the OWSN, the optical fiber refractive index in the OFTN, and the end-to-end propagation distance over the OWSN, i.e., the propagation distance between source and destination points (or satellite ground stations) in different cities over the OWSN.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In [14], crossover functions were proposed to enable the calculation of the crossover distance in four different scenarios. It was concluded that the crossover distance depended upon the altitude of satellites in the OWSN, the optical fiber refractive index in the OFTN, and the end-to-end propagation distance over the OWSN, i.e., the propagation distance between source and destination points (or satellite ground stations) in different cities over the OWSN.…”
Section: Related Workmentioning
confidence: 99%
“…However, a direct LISL was assumed to exist between the ingress and egress satellites, which is usually not the case in OWSNs arising from real satellite constellations. In this work, we extend the crossover function for the first scenario proposed in [14] to conform it to a more realistic scenario to enable a more realistic determination of the crossover distance by incorporating intermediate satellites between ingress and egress.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Free-space optical communication is receiving more and more attention these days as it is a promising and rapidly developing technology for wireless communication between satellites due to its larger link bandwidth, license free spectrum, higher link data rate, better security, smaller antenna size, lower terminal mass, and lower terminal power consumption compared to radio frequency-based satellite communication [1]. The free-space optical satellites networks (FSOSNs) based on upcoming low Earth orbit (LEO) satellite constellations, such as SpaceX's Starlink [2], and Telesat's Lightspeed [3], are expected to employ optical or laser inter-satellite links while optical or laser uplink and downlink communications are envisioned for future FSOSNs [4], [5].…”
Section: Introductionmentioning
confidence: 99%